1971
DOI: 10.4141/cjps71-097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Practices on Foliage and Root Development, Digestibility, Cold Hardiness and Nodulation of Birdsfoot Trefoil

Abstract: Empire, Leo, Viking and Wallace cultivars of birdsfoot trefoil were evaluated in a greenhouse experiment for total forage production, aerial and root growth, in vitro digestibility, cold hardiness, etiolated regrowth and modulation. Plants were harvested at the vegetative stage (four harvests); 10% bloom (three harvests); 50% bloom (two harvests); and maximum growth (one harvest), at two stubble heights, 2.5 and 7.5 cm. Harvesting at the maximum growth stage produced the most dry matter but the lowest digestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Langille and Calder (1971) reported more nodulation on birdsfoot trefoil (Lotus corniculatus L.) with a decreased frequency of harvests.…”
Section: Soil Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Langille and Calder (1971) reported more nodulation on birdsfoot trefoil (Lotus corniculatus L.) with a decreased frequency of harvests.…”
Section: Soil Factorsmentioning
confidence: 99%
“…After cut ting, however, these nodules were replaced by new ones lo cated on the tap root as well as by nodules on the lateral root branches farther belpw the soil surface. Langille and Calder (1971) studied birdsfoot trefoil (Lotus corniculatus L.). When harvested at a height of 7.5 cm rather than at 2.5 cm, there were significantly more nodules per plant.…”
Section: Cutting Managementmentioning
confidence: 99%
“…They also stated that increased harvest frequency lowered the root weight. Workers in Canada found that root weights decreased as cutting frequency increased, regardless of cultivar or stubble height (Langille and Calder, 1971 ). Other researchers reported a difference in root weight in response to harvest treatments by different germplasms of birdsfoot trefoil (Pierre and Jackobs, 1953).…”
mentioning
confidence: 99%
“…Birdsfoot trefoil can tolerate many growing conditions, can grow where soil properties or environmental conditions make alfalfa production difficult, and will grow under drought conditions (Beuselinck and Grant 1995;Undersander et al 1993). The nutritive value of BFT has been suggested to be equal to or greater than that of alfalfa (Langilee and Calder 1971;Marten and Jordan 1979). The purpose of this study was to evaluate tree and forage species common to the central Great Plains, as to their potential in silvopasture systems.…”
Section: Introductionmentioning
confidence: 99%